Interspecific Competition Between Eotetranychus sexmaculatus Riley and Oligonychus biharensis Hirst (Acari: Tetranychidae) - Lijiu Zheng; Yong Zhang; Xia Shi; Wei Gan; Fangping Zhang; Yueguan Fu; Ya Liu; Junyu Chen; Zhengpei Ye (Insects)
Eotetranychus sexmaculatus has long been recognized as an important spider mite pest of rubber trees. Recently, increasing damage from Oligonychus biharensis has elevated its importance as a key spider mite pest. These two species share highly overlapping ecological niches, with outbreaks strongly associated with high temperatures and drought stresses. However, little is known regarding the potential competition between these spider mite species and the role of temperature in shaping these interactions. This study investigates the development and reproduction of E. sexmaculatus and O. biharensis at varying population densities, and evaluates their dynamics at 27 °C, 30 °C, and 33 °C. Five initial population densities of E. sexmaculatus and O. biharensis were evaluated in mixed populations: 0:30, 10:20, 15:15, 20:10, and 30:0. The results demonstrate both intra- and interspecific competition between E. sexmaculatus and O. biharensis. At all three intraspecific densities, the survival rate and lifespan of both species declined as density increased, with fecundity also decreasing at higher densities. Single-species populations of each mite were larger in number when compared with mixed populations. Across all treatments, the mean and peak values of the intrinsic rate of increase (rm) were greater in O. biharensis than in E. sexmaculatus. Additionally, increasing temperatures accelerated the displacement of E. sexmaculatus by O. biharensis, regardless of the initial population density. When the mixed populations of E. sexmaculatus and O. biharensis were at densities of 10:20, the highest interspecific competition coefficients were obtained at 33 °C, with values of 0.6591. In conclusion, O. biharensis consistently outcompeted E. sexmaculatus at all tested temperatures, irrespective of initial densities, providing valuable insights into the competitive dynamics of dominant rubber tree pests.